2017
DOI: 10.1002/aoc.3786
|View full text |Cite
|
Sign up to set email alerts
|

Two two‐dimensional supramolecular copper(II) and cobalt(III) complexes derived from a new quinazoline‐type ligand: Syntheses, structures, and spectral, thermal, electrochemical and antimicrobial activity studies

Abstract: Two two‐dimensional supramolecular copper(II) and cobalt(III) complexes, Cu(L1)2 (1; HL1 = 2‐hydroxy‐3‐methoxybenzaldehyde oxime) and [Co(L2)2]2⋅2CH3COOCH2CH3 (2; HL2 = 1‐(2‐{[(E)‐3‐methoxy‐2‐hydroxybenzylidene]amino}phenyl)ethanone oxime), have been synthesized via complexation of Cu(II) nitrate trihydrate and Co(II) acetate tetrahydrate with HL. A plausible reaction mechanism for the formation of HL1 is proposed. HL was synthesized and characterized using infrared, 1H NMR and 13C NMR spectra, as well as elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…[61] Simultaneously, the negative values between HOMO and LUMO frontier orbitals manifested complexes were relatively stable. [62]…”
Section: Theoretical Investigationsmentioning
confidence: 99%
“…[61] Simultaneously, the negative values between HOMO and LUMO frontier orbitals manifested complexes were relatively stable. [62]…”
Section: Theoretical Investigationsmentioning
confidence: 99%
“…In previous work, several studies on the properties of copper (II) and cobalt (II) complexes have been reported. [19,20] As an continuation of our research, herein we mainly report synthetic routes (Scheme 1), characterization and biological activity of complexes [Zn (L) 2 (CH 3 OH) 2 ](NO 3 ) 2 (1) and [Ni(L) 3 ]Á(NO 3 ) 2 (2) with 2-(2-imidazolyl)-4-methyl-1,2-dihydroquinazoline-N 3 -oxide ligand (L). Zn (II) and Ni (II) complexes were characterized by X-ray crystallographic analysis and in both the metals show a six-coordination geometry.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of application, the complexes derived from these two different types of ligands have potential value in the fields of biochemistry, catalysis, luminescence, and so forth. [17] We continue our interest to study the coordination behavior and properties of transition metal complexes that are derived from some quinazoline-type ligands [18,19] ; as an extension of our investigations, in this paper we, explored two 3-D supramolecular cadmium (II) and nickel (II) complexes: [Cd(L) 2 (NO 3 ) 2 ] (1) and [Ni(L) 2 (OH) 2 ][Ni (L) 2 (CH 3 OH) 2 ](NO 3 ) 2 ÁCH 3 OH (2) (L = 2-[2-pyridyl]-4-methyl-1,2-dihydroquinazolin 3-oxide) were synthesized via complexation of cadmium nitrate tetrahydrate and nickel nitrate hexahydrate with the new quinazoline-type ligand L. X-ray crystallography indicated that both complexes emerged slightly distorted octahedral geometry with six-coordinated environment. It was worth noting that in the crystal structures of complexes 1 and 2, 1 assembled into an infinite 1-D chain-like, 2-D network and 3-D supramolecular skeletons, while 2 was presented infinite 1-D chain, fishnet-like 2-D and W-shape 3-D structures.…”
Section: Introductionmentioning
confidence: 99%